The relationship among sleep quality, sleep-related behaviour and personality traits in older schoolchildren - Vosylis, Rimantas; Perminas, Aidas; Žukauskienė, Rita (Psichologija, 2009)
Objectives. Adolescence is a period of various physical, cognitive activities, emotional and social alterations, which need additional bodily resources and naturally good and sufficient sleep for renewing these resources. However, increased requirements in school, new social interests, biological alterations make adolescents’ sleep not sufficiently long and qualitative enough, so achievements at school and the quality of life generally suffer. There are a lot of researches on this topic in foreign countries, but we couldn’t find any in Lithuania. Little research, both in Lithuania and abroad, has been done on personality and sleep quality relations in adolescence and on how personality traits can be related to sleep quality, how this relation can be affected by sleep-related behaviour. Purpose. To evaluate the relationship of personality features to sleep quality and sleep-related behaviour in older schoolchildren. The research involved 88 boys and 124 girls from two Kaunas schools. Methods. A questionnaire was prepared to evaluate sleep quality. It contained 31 questions concerning various sleep quality aspects. Four indices (troubles in falling asleep, night rest satisfaction, daytime fatigue, habit to sleep in the daytime) were selected after a factor analysis. Additionally, 12 questions concerning sleep-related behaviour were asked, from which four indices (use of psychoactive substances, sport, PC games and watching TV, relaxation activity before sleep) were constructed after factor analysis and used in this study. The NEO PI-R questionnaire was used to measure personality traits. Results. In boys and girls, neuroticism is related with the difficulties of falling asleep and less satisfaction with night’s rest independently of sleep-related behaviour. Girls’ openness to experience is related to daytime fatigue, and their extraversion and smaller agreeableness are related with difficulties of falling asleep, but this association is affected by the use of psychoactive substances. Boys’ conscientiousness is related to daytime sleeping, but this relation is affected by engaging in sport activities. Girls’ engagement in the activities that help relax before sleep is related to their higher conscientiousness, higher agreeableness, more frequent difficulties with falling asleep and daytime sleeping. Boys’ extraversion, openness, agreeableness and sleep quality are not related to each other.